Writing around War: Parapolemics, Trauma, and Ethics in Ukrainian Representations of the War in the Donbas - Blacker, Uilleam (East/West, 2022)
The article considers a range of literary texts about the war in Donbas and argues that one of the primary representational strategies employed by Ukrainian writers has been the use of “parapolemics.” The article operates with Kate McLoughlin’s definition of this term as a focus on the “outskirts” of armed conflict, but also relates the idea to concepts drawn from trauma studies. While, on the one hand, the use of parapolemics may be a way of avoiding direct representation of wartime violence and death, the opportunities it affords are extremely valuable: focusing on the “backstage” of war and eschewing direct representation of violence allows writers to explore otherwise marginalized, and highly complex, dimensions of wartime experience. At the same time, connecting the parapolemic approach to ideas taken from trauma theory, particularly relating to empathy and responsibility, allows us to understand how parapolemics provide a way of reflecting both on the ethics of representing war and the of self-other relationships that arise in wartime.